ANALISIS SELF CONTROL, PENGETAHUAN KEUANGAN, DAN PENGALAMAN KEUANGAN TERHADAP PERENCANAAN INVESTASI - Sumaryanto, Untung Sriwidodo & (Universitas Slamet Riyadi, 2018)
Investment planning is an act of allocating a number of funds currently made inthe hope of obtaining future income. Investment planning is an important thing that isowned by people who have a fixed income so that the income derived from the results oftheir work can be useful for their future. The population in this study were permanentincome people in Jaten Village, Karanganyar Regency. The sampling technique usesporous sampling and snowball sampling, a sample used by 100 people. Data collectiontechniques using: questionnaire. Data analysis using classical assumption test, multiplelinear regression, t test, F test, and determination coefficient. The results obtained by theconclusion: Hypothesis 1 which states that: There is a significant effect of self-control oninvestment planning in the fixed income community in Jaten village, KaranganyarRegency, proven to be true. Hypothesis 2: which states that: There is a significantinfluence of financial knowledge on investment planning in fixed income communities inJaten village, Karanganyar Regency, proven to be true. Hypothesis 3 states that: Thereis a significant effect of financial experience on investment planning in the fixed incomecommunity in Jaten village, Karanganyar Regency, proven to be true.Keywords: self control, financial knowledge, financial experience, investment planning.